2021
DOI: 10.1055/s-0041-1736397
|View full text |Cite
|
Sign up to set email alerts
|

Role of Radiographs and Ultrasound in Diagnosing Calcific Tendinitis and Periarthritis in the Wrist and Hand with Ultrasound-Guided Barbotage as Management Tool

Abstract: Aim To demonstrate the role of radiographs and ultrasound (USG) in the diagnosis of calcific tendinitis and periarthritis in the wrist and hand and the efficacy of USG-guided barbotage for its management. Materials and Methods A retrospective chart review was performed in six patients who presented with acute-onset pain in the wrist and hand varying from 3 days to 2 weeks. Four patients had tenderness over pisiform and two patients had pain along the lateral aspect of the wrist and thumb. Radiographs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Cross-sectional imaging plays a crucial role in the diagnosis of wrist conditions and allow targeted management of the wrist pain. 20,21 CT can help better delineate calcification in comparison to radiographs and focused high-resolution sequences can be undertaken to reduce radiation. US imaging provides a noninvasive modality for assessing wrist conditions avoiding radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional imaging plays a crucial role in the diagnosis of wrist conditions and allow targeted management of the wrist pain. 20,21 CT can help better delineate calcification in comparison to radiographs and focused high-resolution sequences can be undertaken to reduce radiation. US imaging provides a noninvasive modality for assessing wrist conditions avoiding radiation.…”
Section: Discussionmentioning
confidence: 99%
“…It also helps in giving information on the nature of the calcification, whether it’s hard or soft. Doppler utility can also determine whether the calcification is in the acute or chronic phase [ 14 ]. With dynamic ultrasonography available in our outpatient clinic, we found calcification on the FCU tendon before confirming with X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…Injection using local anesthetics, with or without corticosteroid has shown to be effective, with the complete resolution within 6 days [ 5 ]. A series done by Ahuja et al, has shown that ultrasound guided barbotage, has been shown to be effective with immediate improvement of symptoms [ 14 ]. Splinting has also shown to be effective as it shortens the span of pain to 12 days, and it is what was done to our patient and has shown good result [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the condition tends to resolve on its own without treatment, administration of prednisone and a steroid injection in combination with splinting has been shown to decrease the duration and severity of symptoms [10] . Use of ultrasound during said injection may aid in locating the deposit [11] . It is of utmost importance to carry out a thorough physical examination, laboratory work-up, and diagnostic imaging to ensure that the correct diagnosis is made, given the rarity of this condition developing in the wrist in current literature.…”
Section: Review Of the Literaturementioning
confidence: 99%